Mid term effects of pulmonary thromboendarterectomy on clinical and cardiopulmonary function status. Issue 7 (1st July 2002) - Zoia, M C; D'Armini, A M; Beccaria, M; Corsico, A; Fulgoni, P; Klersy, C; Piovella, F; Viganò, M; Cerveri, I
Abstract : Background: Chronic thromboembolic pulmonary hypertension (CTEPH) can be successfully treated surgically by pulmonary thromboendarterectomy (PTE) but there are few data on mid-term cardiopulmonary function, particularly on exertion, and clinical benefits following pulmonary PTE. Methods: A 2 year follow up study was undertaken of clinical status, haemodynamic and lung function indices, gas exchange, and exercise tolerance in 38 patients of mean (SD) age 50 (15) years who had undergone PTE. Results: In-hospital mortality was about 10%. Before PTE all the patients were severely impaired (NYHA classes III–IV). There was no time difference in the improvement in the parameters: nearly all the improvement in cardiac output, gas exchange, and clinical status was achieved in the first 3 months as a result of the relief of pulmonary obstruction. At 3 months the percentage of patients with normal cardiac output and Pao 2 and of those with reduced clinical impairment increased to 97%, 59%, and 87%, respectively, without any further change. Only mean pulmonary artery pressure (mPAP), carbon monoxide transfer factor (Tlco ), and exercise tolerance improved gradually during the second year, probably due to the recovery of the damaged small vessels. Tlco was overestimated before PTE but afterwards the trend was similar to that of mPAP. Conclusions: At mid term only a few patients did not have a satisfactory recovery because of lack of operative success, hypertension relapse, or the effect of preoperative hypertension on vessels in non-obstructed segments. Most of the patients, even the more compromised ones, had excellent long lasting results.